2004
DOI: 10.1029/2004rs003039
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetry of auroral kilometric radiation with a triaxial nonorthogonal antenna system

Abstract: [1] The response of a triaxial nonorthogonal radio-polarimeter on board a spinning spacecraft has been analyzed in order to determine effective length vectors of its short electric antennas. In the ideal case all three antennas of a radio-polarimeter would be orthogonal to each other. In practice, their electric axes do not coincide with the physical ones. It is shown that effective length vectors of the antennas can be found by fitting theoretical temporal variations of the Stokes parameters to those determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Results concerning AKR beaming presented in this paper are based on single-satellite AKR observations (POLRAD experiment on board the Auroral Probe in the frame of Interball project). With our swept frequency analyzer we are not able to work with individual AKR bursts generated in small elementary sources, but it is still possible to determine the direction to the AKR source region and confirm in this paper AKR beaming found by Mutel et al [2008] using ⃗ k vector source location scheme [Panchenko, 2003].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Results concerning AKR beaming presented in this paper are based on single-satellite AKR observations (POLRAD experiment on board the Auroral Probe in the frame of Interball project). With our swept frequency analyzer we are not able to work with individual AKR bursts generated in small elementary sources, but it is still possible to determine the direction to the AKR source region and confirm in this paper AKR beaming found by Mutel et al [2008] using ⃗ k vector source location scheme [Panchenko, 2003].…”
Section: Introductionsupporting
confidence: 56%
“…POLRAD's direction finding capacity is based on the instantaneous AKR power densities measurements on all three antennas [Panchenko, 2003], assuming that AKR is circularly polarized and originates from a point source. Recent measurements by Panchenko et al [2008] and Lamy et al [2010] found no conclusive presence of linearly polarized AKR component.…”
Section: Akr Sources Direction Finding-methodsmentioning
confidence: 99%
“…The full set of GP measurement is thus recorded. GP inversions have been built and used on these data to characterize the AKR (Hanasz et al 2003;Panchenko 2004). …”
Section: Spin Demodulation Goniopolarimetrymentioning
confidence: 99%
“…The methodology of this calibration is well described in Vogl et al []. The method has successfully been applied to derive the antenna properties of radio experiments on board, e.g., ISEE‐3 [ Fainberg et al , ], Voyager [ Lecacheux and Ortega‐Molina , ; Wang and Carr , ], Interball‐2/Polrad [ Panchenko , ], or Cassini [ Vogl et al , ; Cecconi and Zarka , ].…”
Section: Introductionmentioning
confidence: 99%